Soil water bioengineering to help improve the ecological connectivity of river banks - BONCOURT, Étienne; EVETTE, André; BERGÈS, Laurent; ALP, Maria (INRAE, 2024)
In urban areas, rivers and riparian ecosystems are often the only ecological corridors available for the movement of wildlife. Riverbanks are often stabilised by civil engineering works, which can lead to habitat degradation and loss of landscape connectivity. Soil water bioengineering structures are an alternative to riprap, as they maintain the quality of natural ecosystems using native plant species instead of rocks, but their potential positive impact on animal movements remains poorly understood. With the GéniTrame project, we designed a method enabling river managers to assess the potential gain in connectivity thanks to soil water bioengineering. Using four target vertebrate species with a wide range of dispersal abilities, we used landscape graphs to assess habitat connectivity under different contrasting riverbank scenarios. We showed that the restoration of small, well-chosen stretches of riverbank by means of soil water bioengineering structures could lead to major gains in connectivity for some species (beaver, common toad) but no gain for others (common sandpiper, ring-necked snake). The method used could help river managers wishing to integrate the landscape connectivity dimension into riverbank restoration work. Dans les zones urbanisées, les rivières et les écosystèmes riverains sont souvent les seuls corridors écologiques disponibles pour le déplacement de la faune. Cependant, les berges y sont souvent stabilisées par des ouvrages de génie civil, ce qui peut entraîner une dégradation de l'habitat et une perte de connectivité de ces habitats à l'échelle du paysage. Les ouvrages de génie végétal sont une alternative aux enrochements, car ils maintiennent la qualité des écosystèmes naturels en utilisant des espèces végétales indigènes au lieu de rochers, mais leur impact positif potentiel sur les mouvements d’animaux associés aux écosystèmes riverains reste mal connu. Avec le projet GéniTrame, nous avons conçu une méthode permettant aux gestionnaires de rivières d’évaluer le gain de connectivité ...